The Effect of Exports, Government Expenditures and Inflation on Economic Growth in Central Kalimantan - Sabirin Sabirin; Ahmad Rizani; Desy Safitri (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
This study analyzes how the partial and simultaneous influence of the components of exports, government spending and inflation on economic growth. The method used in this research is descriptive-quantitative approach. The data used in this study is time series data for 2010-2019 in the quarter period in Central Kalimantan Province. The collected data is then analyzed using Multiple Linear Regression, the software used is Eviews version 9. The results of this study indicate that partially exports have a negative and insignificant effect on economic growth. Government Expenditure partially has a negative and insignificant effect on Economic Growth. Inflation partially positive and significant effect on economic growth. And overall Exports, Government Expenditures, and Inflation simultaneously have no effect on Economic Growth.